Cytokines, adipocytokines and inflammatory markers in patients on continuous ambulatory peritoneal dialysis and hemodialysis. (8th August 2016) - Oncel, Mufide; Akbulut, Seval; Toka Ozer, Turkan; Kiyici, Aysel; Keles, Mustafa; Baltaci, Beyhan; Turk, Suleyman
Abstract: Background: Cytokines are essential mediators of immune response. Chronic renal failure patients suffer from chronic inflammation that results from factors such as impaired renal function, accumulation of uremic toxins and bio incompatibility of dialyzer membranes. These patients are also at increased risk of cardiovascular diseases. We have evaluated cytokines, adipocytokines and inflammatory markers in patients with chronic renal failure undergoing hemodialysis (HD) and continuous ambulatory peritoneal dialysis (CAPD). Material and methods: We have determined serum tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), high-sensitivity C-reactive protein (hsCRP), leptin and ghrelin levels of chronic renal failure patients treated with either HD ( n = 20) or CAPD ( n = 20). TNF-α, IL-6, ghrelin and leptin measurements were performed by commercially available kits based on enzyme-linked immunosorbent assay (ELISA) method. hsCRP levels were determined by turbidimetric methods. Results: Serum TNF-α and IL-6 levels of patients on HD were significantly higher than those of the ones on CAPD ( p < 0.05). Ghrelin, leptin and hsCRP concentrations were similar in both groups. Conclusions: We can conclude that cytokine production is more obvious in HD process.